Gastrointestinal tract at high altitude of Ladakh: a surgeon’s perspective - Deskit, Padma (International Surgery Journal, 2026)
Background: High altitude environment with its hypoxic rarefied, cold, dry and high wind velocity affect almost all aspect of human physiology. However, attitude sickness is generally equated with HACE and HAPE. At high altitude, cellular hypoxia is found to have profound effect on the Gastrointestinal Tract (GI), which otherwise is mostly ignored. It is estimated that 80% of people who have acute mountain sickness have GI symptoms. The spectrum of GI dysfunctions which occur at high altitude are wide and varied but still not commonly talked about unlike HACE and HAPE. Methods: The present study is a post-facto, retrospective in nature where observations and data are collected during April 2023 to April 2024, at SNM Hospital, Leh in Ladakh (UT) of India (the only government hospital in Leh), located at an altitude of 3000 meter AMSL. Data collected is based on the patients who had reported to emergency and OPD of SNM hospital with gastrointestinal ailments which are conventionally attributed to short and long term stay at high altitude. In addition, some unique conditions which has been managed by the author at different time frame are also reported in this study, because of they being rare, unique and challenging for a clinician and to further substantiate this study. Results: This study unveiled some unique observations found in high altitude Ladakh region in gastrointestinal context, and some of which were: peptic ulcer perforation was more common than GI bleed. Of the 29 cases of peptic ulcer perforation operated, 19 were lowlanders (65.5%); GI bleed due to peptic ulcer was never seen in both the lowlanders and locals unlike the study from Tibet; carcinoma stomach is the most common malignancy in Ladakh, the figure of 54 number of patients in a year (2023) against the 1.3 Lakh total population of Leh district is comparable to the high incidence rate reported in Mizoram, the state with highest incidence of carcinoma stomach. This rate is definitely higher than the national average; four cases of mesenteric ischemia is reported which otherwise due to venous thrombosis is a rare occurrence and no report of high altitude induced mesenteric venous ischemia is available in literature. Similarly splenic abscess was also seen in some of the tourist visiting Ladakh. Conclusions: High altitude related conditions are needed to be seen and understood through a wider lens and not just HACE and HAPE. Understanding and sharing of experience of high-altitude related condition is essential for further understanding of the topic under discussion. Keeping in view the wide spectrum of gastrointestinal dysfunction occurring in both local and visitor there is need to talk about it on equal footing like HACE and HAPE.